Theoretical principles of formation the platform of systemic interactions of land resource and market cycles of development - Tretiak, N.; Sakal, O.; Lobunko, Yu. (Land Management, Cadastre and Land Monitoring, 2020)
Global trends in the development of economic theory and methodology today demonstrate to the urgent need to formulate a new conceptual framework for economic relations, regulate them, conduct a new economic policy, and turn to the newest vision of economic practice, in particular in the field of nature using. The above factors also determine the choice of research direction for the systemic interaction of land resource and market cycles of development.The purpose of this article is to investigate the conceptual foundations of forming a platform for systemic interactions between the land-resource and market cycles of development to ensure social well-being and sustainable spatial development of the country. The achievement of this purpose necessitated the following tasks: to define the goals, the aim of the platform of systemic interactions of the land resource and market cycles of development and to determine the structure of the interconnected elements of the platform at the national level.As a result, the theoretical principles of formation a platform of systemic interactions of land resource and market cycles of development are investigated; in particular the identification of its system characteristics is made in the article. The structure of the interconnected elements of the system interaction platform at the national level is outlined. The goals and purpose of its functioning are determined and the aim of the first one to achieve the goal – to ensure public well-being and sustainable spatial development of the country is justified, as well as the functions of the platform of systemic interactions of land resource and market cycles of development at the national level.Key words: platform, land-resource and market cycles of development, public welfare, sustainable development.